Parents' perspectives on the appropriateness of a parent-delivered intervention for improving the social play skills of children with ADHD - Wilkes-Gillan, S.; Bundy, A.; Cordier, Reinie; Lincoln, M.; Hancock, N. (The College of Occupational Therapists - UK, 2015)
Introduction: This study aimed to evaluate parents’ perspectives of the appropriateness of a parent-delivered play-based intervention, The Ultimate Guide to Making Friends. The intervention was designed to improve the social play skills of children with ADHD.Method: One month post-intervention, seven parents of children with ADHD participated in individual semi-structured interviews.Interviews ranged from 40–60 minutes. Parents were asked about their perceptions of the intervention: experience, benefits,logistics that supported or hindered participation and satisfaction with the intervention for themselves and their children. Datawere analysed thematically using constant comparative methods, whereby two researchers worked independently to analyseemergent themes.Findings: Thematic analysis revealed a single core theme of reframing: a process whereby both parents and their children wereassisted to develop new perspectives regarding their social skills and interactions. The core theme comprised three sub-themes:(1) connecting with the intervention; (2) parent and child benefits resulting from a new perspective; and (3) continued everydayuse of the intervention materials and strategies.Conclusion: The intervention was appropriate from parents’ perspectives. The core theme of reframing and sub-themes collectivelyrelated back to the following aspects of appropriateness: (a) a positive experience; (b) relevant and important to their/theirchild’s needs; (c) beneficial; (d) a socially and ecologically valid approach, fitting their everyday lives; and (e) promoting changethat continued over time.